Natural Dyes for Cotton Fibre - Gopalakrishnan, M.; Anubama, S.; Prasanth, E.; Srinithi, M. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Textile Industry sector is considered to be one of the most polluting sector. In Recent times, the Textile industry is moving towards the Sustainable products and processes. The enlightened awareness of Ecology, Environment and Pollution control encourages the application of Natural resources. This initiates the use of Natural dyes. This paper explains the Dyeing of Cotton Fabric using Natural stuff from various natural materials. There are several process involved in dyeing of fabric. First, the dye extraction from the natural material. Since it is natural dye, Mordanting should be done. The Mordant used are Copper Sulphate, Aluminum Sulphate and Potassium Dichromate. Mordant will enhance the Fastness properties of naturally dyed materials.
Keywords: Natural Dye; Coconut Root; Mordant; Fastness Properties